LIFE STRUGGLE AS REFLECTED IN JOHN STEINBECK’S THE GRAPES OF WRATH - Sry S Langi Toding; Tini Mogea; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2023)
In this study, the writer analyzed the novel written by John Steinbeck, entitled The Grapes of Wrath. This novel tells about the struggle of the Joad family in fulfilling their needs in life. Therefore, the writer gave the title of this skripsi with “Life struggle as Reflected in John Steinbeck’s The Grapes of Wrath.” In this research, the writer used objective approach by Abrams. The writer of this study used Abrams' objective methodology. Because the data in this study are quotes from the novel The Grapes of Wrath and because there is no statistical analysis or consideration of numbers, it is categorized as descriptive qualitative approach. Firstly the result of this study shows the struggle for a place to live refer about Joad family migrates from their native land to another place to live better. Second, struggle to find work refers the Joad family hard struggle to survive and struggle to find work in their new place. Their expectation about California is really different in reality. The third, struggle to security, it is about how Joad family protects their member of family, Tom Joad, from the police because he has killed one of the police. In this study, the writer analyzed the novel written by John Steinbeck, entitled The Grapes of Wrath. This novel tells about the struggle of the Joad family in fulfilling their needs in life. Therefore, the writer gave the title of this skripsi with “Life struggle as Reflected in John Steinbeck’s The Grapes of Wrath.” In this research, the writer used objective approach by Abrams. The writer of this study used Abrams' objective methodology. Because the data in this study are quotes from the novel The Grapes of Wrath and because there is no statistical analysis or consideration of numbers, it is categorized as descriptive qualitative approach. Firstly the result of this study shows the struggle for a place to live refer about Joad family migrates from their native land to another place to live better. Second, struggle to find work refers the Joad family hard struggle to survive and struggle to find work in their new place. Their expectation about California is really different in reality. The third, struggle to security, it is about how Joad family protects their member of family, Tom Joad, from the police because he has killed one of the police.